AKTUALISASI MAKNA SYARÎ’AH DAN FIQH DALAM KONSEP HUKUM ISLAM - Bustami Saladin (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
Islamic law is in accordance with its dimension in a history, that makes the content of the study in its dimension always appears any system or method. That’s why in Rasulullah saw era, Islamic law is based on Allah swt’s revelation and Rasulullah’s judgment, namely, Islamic law in Alquran and Sunnah perspectives. The purpose of declaring Islamic law is applying and protecting the benefit for people. It is applied in Islamic law that concerns all aspects of human life that has three aspects: dharûriyah (primary), hajiyah (secondary), and tahnisiyah (complementary).